PENGARUH KEBIJAKAN DIVIDEN, KONSENTRASI KEPEMILIKAN DAN LIKUIDITAS TERHADAP KEBIJAKAN HUTANG SERTA KONSEKUENSINYA TERHADAP NILAI PERUSAHAN (Studi kasus pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) pada periode 2010-2013) (Students' Journal of Economic and Management, 2015)
This study aims to test the effect of dividend policy, ownership concentration, and liquidity to debt policy, than consequently it to the firm value in manufacturing companies listed on the indonesia stock exchange (IDX). In this study population are used the manufacturing companies listed on the Indonesia Stock Exchange (IDX) of the years 2010 to 2013. The sampling technique using purposive sampling. Data testing use a multiple linier regression analysis.The analysis showed that liquidity and ownership concentration having negative effect significantly to debt policy, while dividend policy has no significant effect on det policy, and than debt policy have a negative effect significantly to the firm value. Keyword : Divident policy, Ownership concentration,Liquidity, Debt policy, Firm value